Covalent Conjugation of 2-Hydroxyethylmethacrylate with an Anti-Biofouling 2-Aminoimidazole Small Molecule and its Effect on an Experimental Dental Adhesive - Hampton, Joseph R (East Carolina University, 2023)
Secondary caries, or cavities that have re-infected previously restored teeth, are a prevalent problem in the oral health community. An overwhelming 74% of restored teeth require further work and replacement restorations; many of which are due to patient's lack of oral hygiene and knowledge. Often, the initial carious tissue is due to lack of oral hygiene and after procedural restorations, no changes occur in their daily routine. This certainly contributes to the replacement rate; however, the remaining portion is due to the lack of preventative measures in the current methacrylate resin composite materials clinically utilized. Thus, there is a critical need to produce a dental adhesive with preventative characteristics. Which can reduce the high rate replacement for such materials. To create such a dental adhesive, a 2-aminoimidazole (2-AI) motif derived from sea sponges that has shown capabilities of disrupting bacterial biofilms has been chemically conjugated to 2-hydroxyethyl methacrylate (HEMA, 1), a methacrylate commonly used in dental adhesives. Briefly, boc-protected 2-aminoimidazole (8) was coupled to a commercially available alkyne using standard conditions of amide formations. In the key step of the synthesis, the alkyne (9) was subjected to a "click" reaction with the known azide (3) and pushed through HPLC for separation. Under the pressure of HPLC and the presence of TFA, the product was deprotected and the final product was prematurely synthesized. At this stage, the solid functionalized methacrylate product (10), was incorporated into a control group polymer blend to produce an experimental dental adhesive. When co-polymerized at 1mM concentration, no significant differences in the mechanical properties were determined between control, commercial and experimental groups. The polymer also displayed similar degrees of conversion amongst groups and were slightly increased compared to literature values of the commercial adhesive Clearfil SE Protect. Additionally, the new monomer showcased anti-biofouling properties, however, when incorporated at 10 mM concentration into the polymer blend, no bacterial depletion was noted.
Keywords: Anti-Biofouling; Secondary Caries; Dental adhesives; Fouling--Prevention; Dental caries--Prevention